A case with rare manifestation of Cronkhite-Canada Syndrome with remission after treatment and literature review - Patel Dharmik; Tripathi Kaushalendra Mani (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2018)
Cronkhite-Canada syndrome is a rare disorder which is sporadic in nature, its pathology and cause is not fully understood, usually characterized by the presence of polyps in the stomach and large intestine and less frequently in the oesophagus with associated, the aim of this report is to discuss the pathogenesis of this syndrome and possible treatment options, in this case there was a non-conventional approach applied to this with a good prognosis, the disease itself is usually present among the Japanese population with a male to female ratio 2:1 but was of irrelevance as our patient was Indian, this report will also shed some light on the use of herbal medicine and its application in the treatment of this disease along with conventional medicine.